2020
DOI: 10.3389/fmed.2020.00424
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmune Mechanisms in Signaling of Pain During Acute Kidney Injury (AKI)

Abstract: Acute kidney injury (AKI) is a significant global health concern. The primary causes of AKI include ischemia, sepsis and nephrotoxicity. The unraveled interface between nervous system and immune response with specific focus on pain pathways is generating a huge interest in reference to AKI. The nervous system though static executes functions by nerve fibers throughout the body. Neuronal peptides released by nerves effect the immune response to mediate the hemodynamic system critical to the functioning of kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 155 publications
(192 reference statements)
0
2
0
Order By: Relevance
“…This inflammasome, upon activation, overexpresses cleaved caspase-1 and mature IL-1β, resulting in NEU recruitment and the consequent progression of AKI (Danielski et al, 2020). Our results suggested that HSC decreased the expression to the AKI-associated inflammatory response (Gupta et al, 2020).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This inflammasome, upon activation, overexpresses cleaved caspase-1 and mature IL-1β, resulting in NEU recruitment and the consequent progression of AKI (Danielski et al, 2020). Our results suggested that HSC decreased the expression to the AKI-associated inflammatory response (Gupta et al, 2020).…”
Section: Discussionmentioning
confidence: 66%
“…In addition, HSC inhibited the serum and kidney production of pro‐inflammatory cytokines TNF‐α, IL‐6, and IL‐1β in LPS‐stimulated AKI. TLR4 is proven to govern the PIP2 pathway, influencing the release of intracellular calcium and contributing to the AKI‐associated inflammatory response (Gupta et al, 2020). We observed that TAK‐242 could inhibit PIP2 and PLCγ2 protein expression.…”
Section: Discussionmentioning
confidence: 99%